Library Users’ Perceptions of Collection Organization at the Regional Archives and Library Agency of West Sumatra Province - Santikha, Annisa Dwi; Rahmah, Elva (Darul Yasin Al Sys, 2026)
Collection arrangement is an essential component of library management because it directly affects information retrieval effectiveness and service quality. However, practical problems such as inconsistent call numbers, inaccurate shelving, and discrepancies between catalog records and the physical location of materials may hinder users in accessing information and shape their perceptions of library services. This study aims to describe library users’ perceptions of collection arrangement at the Regional Archives and Library Service of West Sumatra Province. A quantitative approach with a descriptive quantitative method was employed. The population consisted of 33,184 library users, from which 100 respondents were selected through simple random sampling using the Slovin formula. Data were collected through observation, questionnaires, and library research. The research instrument comprised 20 statement items that were tested for validity and reliability using SPSS version 26. The validity test showed that all items had r-count values greater than the r-table value of 0.361, while the reliability test produced a Cronbach’s Alpha coefficient of 0.829, indicating that the instrument was reliable. The findings reveal that users’ perceptions of collection arrangement were categorized as good, with an overall mean score of 3.15. The clarity of the classification system obtained the highest mean score of 3.22, whereas the accuracy of collection arrangement recorded the lowest mean score of 3.06. These results indicate that call number consistency, classification system clarity, orderly shelving, and ease of information retrieval have adequately supported users in accessing information. The study concludes that collection arrangement is not merely a technical library activity but also a strategic factor in improving service quality and information accessibility. These findings provide practical implications for libraries in improving shelving accuracy, maintaining consistency in collection organization, and optimizing information retrieval systems to develop more effective and user-oriented public library services.